FOOD SAFETY AND NUTRITIONAL VALUE OF JINGGO RICE IN THE SANUR TOURISM AREA, DENPASAR CITY - Ayu Agung Rathmaryanti; Ni Putu Agustini; Dr. Ni Komang Wiardani (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2019)
Jinggo rice is one of the traditional foods whose processing doesnt yet have special standards. Bad sanitation processing can increase the occurrence of contamination. Beside that, Jinggo rice as the main food must contain complete nutritional value and contribute to sufficient caloric value. The purpose of this studies to know food safety and nutritional value of Jinggo rice in the Sanur Denpasar City, with descriptive research type and cross sectional design. The sample were 10 nasi jinggo that sold by traders in the Sanur. Data obtained by interviews, observations, and laboratory tests. The results of research that 30% of the samples meets the requirements of the Total Plate Numbers. All samples didnt meet Colifom's requirements, but not contaminated with pathogenic bacteria as E.coli, Salmonella sp, Shigela sp, and Vib cholera. Results of calculation nutritional value and percentage of Jinggo rice calorie donations based on the adequacy of adults according to the RDA are the average energy of jinggo rice 301.43 kcal (14.02%), protein 9.37 grams (16.43%), fat 10,06 grams (16.86%) and carbohydrates 42.54 grams (13.76%). If compared with the standard percentage of nutritional value for main food, one of Jinggo rice doesnt meet the calorie standard. It is hoped that the relevant offices and institutions will provide counseling that sanitation, so that the traders can conduct clean and healthy lifestyle to reduce the occurrence of contamination.Keywords: Jinggo rice, Food safety, Nutritional value